Quality characteristics and stability of chicken cutlet fortified with Fish Protein Hydrolysate (FPH) - Raj, Rehana; Varghese, Shiby; Tabassum, Aisha (Fishery Technology, 2020)
Fish Protein Hydrolysate (FPH) was incorporated inchicken cutlet to study its effect on quality aspectsand storage stability. FPH was added at fourdifferent concentrations viz., 0, 5, 10 and 15%. It wasobserved that 15% FPH in chicken cutlet gave abetter cooking yield of 63.64 Â± 0 .08% and a lowercooking loss of 36.55Â± 0.53%. Hence 15% FPHamong the treatment groups was used for theformulation of chicken cutlet with various proportionsof chicken and binder (60% chicken and 40%potato, 70% chicken and 30% potato, 80% chickenand 20% potato) for optimization. The combinationof 70% chicken and 30% binder exhibited low oiluptake, minimum shrinkage, optimum pH, andoverall acceptability during sensory evaluation(OA). Finally, the optimised combination of 70:30was used to prepare the chicken cutlet and analysedfor the storage stability by MAP and NormalPackaging. It was observed that the oxidativeparameters such as PV, TBARS and TPC were lowerfor the samples which were given MAP. OA washighest for the samples with MAP. It could beconcluded that FPH imparts a positive impact onstorage stability and quality parameters of chickencutlet.